2018
DOI: 10.1186/s13643-018-0756-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of pain management in neurologically injured patients: systematic review protocol of analgesia and sedation strategies for early recovery from neurointensive care

Abstract: BackgroundA recent paradigm shift within the intensive care discipline has led to implementation of protocols to drive early recovery from the intensive care unit (ICU). These protocols belong to a large knowledge, translation and quality improvement initiative lead by the Society of Critical Care Medicine, aiming to “liberate” patients from the ICU. They “bundle” evidence-based elements shown to lower ICU stay and mortality and optimize pain management. The bundled elements focus on Assessing, preventing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Studies in sedated patients under mechanical ventilation have suggested that the inappropriate and heavy use of sedatives is associated with negative consequences, such as prolonged mechanical ventilation, increased hospitalisation and even death (Woodrow, 2011). To improve these results, studies have focused on reducing the infusion of sedatives (Wyler et al., 2018). Mehta and colleagues (2012) argued that the daily discontinuation of sedation infusion (a daily trial without sedation) improves therapeutic outcomes without psychological stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in sedated patients under mechanical ventilation have suggested that the inappropriate and heavy use of sedatives is associated with negative consequences, such as prolonged mechanical ventilation, increased hospitalisation and even death (Woodrow, 2011). To improve these results, studies have focused on reducing the infusion of sedatives (Wyler et al., 2018). Mehta and colleagues (2012) argued that the daily discontinuation of sedation infusion (a daily trial without sedation) improves therapeutic outcomes without psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with delusions, especially the elderly, are susceptible to long-term cognitive dysfunction. These findings suggest that when deciding on the infusion of sedative medications, care should be taken as to the type, dose and purpose of using the drug (Wyler et al., 2018).…”
Section: Introductionmentioning
confidence: 99%